Clinical and radiographic outcomes after antegrade intramedullary nail fixation of humeral fractures. (August 2020) - Mocini, F.; Cazzato, G.; Masci, G.; Malerba, G; Liuzza, F.; Maccauro, G.
Highlights: Among the choices for surgical treatment the most commonly used implants are the locking-compression plate and the intramedullary nailing. The authors performed a clinical and radiographic follow-up in patients underwent antegrade intramedullary blocked nailing for proximal or diaphyseal humeral fractures. Intramedullary nailing with a straight nail of the humerus shows good clinical and radiographic outcomes at 18 months of follow up. ABSTRACT: INTRODUCTION: Humerus fractures are frequent, accounting for about 3-4% of all fractures in adults. Treatment for fractures of the diaphyseal and proximal meta-epiphyseal regions remains controversial: there is no unanimity in the scientific community about the superiority of surgical treatment over non-surgical treatment and which is the best between possible surgical treatments. Among the choices for surgical treatment the most commonly used implants are the locking-compression plate and the intramedullary nailing. The purpose of this study was to perform a clinical and radiographic follow-up in patients who underwent surgical procedures for reduction and osteosynthesis of proximal or diaphyseal humeral fractures by means of anterograde intramedullary nailing with a straight-shaped nail. PATIENTS AND METHODS: A clinical and radiographic follow-up was performed in 56 patients who underwent surgical procedures for reduction and osteosynthesis of proximal or diaphyseal humeral fractures by means of antegrade intramedullary nailing using Synthes MultiLoc® system. Clinical data were collected using subjective quality of life assessment forms (SF12-v2), quality of life related to specific disabilities assessment forms (Quick-DASH, ASES score, WORC) and objective functional assessment forms (Constant-Murley score). The radiographic Follow-Up was performed at 30, 90 and 180 days from the date of the surgery. RESULTS: Almost all patients were able to return to a satisfactory quality of life, comparable with the one before the traumatic episode. The functional results were assessed as excellent or good with almost complete recovery of the range of motion and moderate recovery of strength. The residual pain encountered was moderate or zero. The average QuickDASH score was 17.7 ± 4.3 (range 9.1 - 27.3). The average ASES score was 73.8 ± 8.1 (range 58.3 - 88.3). The average WORC score was 543.3 ± 100 [74% ± 4.8%] (range 310 - 740). The mean Constant-Murley score was 69.6 ± 4.6 (range 61 - 84). All patients had a fair or good consolidation of the fracture on radiographic examinations. The calculated RUST score was 4.2 ± 0.4 (range 4-5) 30 days after surgery, 6.1 ± 0.9 (range 4- 8) 90 days after surgery and 9.8 ± 1.5 (range 7-12) to 180 days after surgery. No major complications were found. CONCLUSIONS: Treatment of the diaphyseal and proximal meta-epiphyseal humeral fractures with antegrade intramedullary nail provides excellent subjective and objective clinical results and good radiographic results. However, clinical studies with larger number of patients and longer follow-up are necessary.